Is a sustainable land-use policy in Germany possible?: insights from an analysis applying the concept of stocks - Fischer, Beate; Jöst, Frank; Klauer, Bernd; Schiller, Johannes (Discussion paper series, 2009)
Land is an essential but limited natural resource. We employ the concept of stocks to analyse driving forces for land-use conversion and to assess, whether the German political "30- hectares-goal" is feasible given the current institutional setting. In this paper major driving forces for land-use conversion are identified and underlying stocks and persistent institutional structures as well as their dynamics are investigated. It will be shown that meeting the 30- hectares-goal is unlikely. We further argue that due to persistent stocks and institutional structures land-use conversion from agricultural into urbanised land takes place on smaller time scales than its reconversion. We conclude that demographic change and regional migration processes may result in further land-use conversion even with declining population. Economic structural change as well as an increasing traffic volume will likewise contribute to further land-use conversion.
Keywords: Graue Literatur